EXCESS AND DEVIATIONS PROPERTIES FOR THE BINARY SOLVENT MIXTURES OF TETRAHYDROFURFURYL ALCOHOL WITH SOME AROMATIC HYDROCARBONS AT 298.15K - AL-HEETIMI, Dhafir Tamween Ajeel; AL-DULAIMY, Zainab Abbas; AL-JAWARY, Asal Ahmed; AL-KHAZRAJY, Omar Sabeeh (Studia Universitatis Babeș-Bolyai Chemia, 2019)
In this work, excess properties (e.g. excess molar volume (VE), excess viscosity (ȠE), excess Gibbs free energy of activation of viscos flow (∆G*E) and molar refraction changes (∆nD) of binary solvent mixtures of tetrahydrofurfuryl alcohol (THFA) with aromatic hydrocarbons (benzene, toluene and p-xylene) have been calculated. This was achieved by determining the physical properties including density ρ, viscosity Ƞ and refraction index nD of liquid mixtures at 298.15K. Results of the excess parameters and deviation functions for the binary solvent mixtures at 298.15 K have been discussed by molecular interactions that occur in these mixtures. Generally, parameters showed negative values and have been found to fit well to Redlich-Kister equation which has been used to obtain the coefficients and evaluate the standard error.